The Impact of Work from Home to Work Life-Balance and Its Implication to Employee Happiness - Elnanto, Johanna Gracelia; Suharti, Lieli (International Journal of Social Science and Business, 2021)
Working from home was an increasing phenomenon to prevent the spread of COVID-19. Although WFH has been expendable well documented, there are still limited studies related to the subject of life balance, happiness and organizational support. This study aimed to figure out the influence of work from home on work-life balance, work-life balance on happiness, and the moderating role of organizational supports towards work from home and work-life balances. The respondents used in this research were the 94 lecturers. The study was done in a quantitative method through cross-sectional data and non-probability sampling method. The analysis model used was Path Analysis, Moderated Regression Analysis and Simple Regression test. The result of this research indicates that WFH has positive effects on WLB and WLB has positive effects on employee happiness. The testing done on moderating effect appeared that organizational support does not moderate the effects of WFH on WLB. Apart from that, theoretical and practical implications were also given in this research. The finding of this study also can be used as managerial practice for any institution and employees to be more aware of their life balances and well-being during the pandemic. For organization, this study can be beneficial to enhance several aspects in making the employees happier. This study also indicates that homeworking could become good alternatives that mutually benefit for both organizations and employees, including flexible work and improving work-life balance.